2022
DOI: 10.1002/pd.6084
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of preimplantation genetic testing for hereditary cancer syndromes: A systematic review

Abstract: Objective To conduct a systematic review of the published literature on clinical outcomes following preimplantation genetic testing for monogenic disorders (PGT‐M) for hereditary cancer syndromes (HCS). Methods Three electronic databases (PubMed, Cochrane, and EMBASE) were searched for publications related to PGT‐M for HCS. When appropriate, weighted means were used to calculate clinical and live birth rates. Results We identified 22 publications that reported on clinical and/or psychosocial outcomes of PGT‐M … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Consequently, the confirmation of a germline variation is used to conduct healthy life-long follow-ups in asymptomatic variant carriers of PMAH families. Furthermore, the diagnosis of an inherited germline mutation in cancer predisposition genes, such as ARMC5 , can be applied in preimplantation genetic diagnosis (PGD) [ 46 , 47 , 48 ] to prevent the occurrence of cancerous patients.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the confirmation of a germline variation is used to conduct healthy life-long follow-ups in asymptomatic variant carriers of PMAH families. Furthermore, the diagnosis of an inherited germline mutation in cancer predisposition genes, such as ARMC5 , can be applied in preimplantation genetic diagnosis (PGD) [ 46 , 47 , 48 ] to prevent the occurrence of cancerous patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, the rate of acceptance of genetic testing among FDRs in mutation‐positive families is very low. Previous research showed that 46%∼70% of members of families with hereditary cancer refused genetic testing in Italy, Australia, Canada and America 7–9 . In China, there are few reports about genetic testing among the FDRs of hereditary cancer patients, while we previously discovered that 48% of the FDRs were informed about hereditary cancer in their families and only 10% of them completed genetic testing.…”
Section: Introductionmentioning
confidence: 88%
“…Previous research showed that 46%∼70% of members of families with hereditary cancer refused genetic testing in Italy, Australia, Canada and America. 7 , 8 , 9 In China, there are few reports about genetic testing among the FDRs of hereditary cancer patients, while we previously discovered that 48% of the FDRs were informed about hereditary cancer in their families and only 10% of them completed genetic testing. These findings clearly indicate that there are still barriers hindering genetic testing for hereditary cancer.…”
Section: Introductionmentioning
confidence: 99%
“…A recent review by Vriesen et al reports that success rates (in terms of CPR, Clinical Pregnancy Rate, and LBR, Live Birth Rate) for CPSs are similar to those of other monogenic diseases [38].…”
Section: Rechitsky Et Al Extended the Technique To Couples With Famil...mentioning
confidence: 93%